Optimization of microwave irradiation demulsifying cutting fluid wastewater and organics’ distribution and transfer - Ling Jie Liu; Su Lin Li; Ru Yue Zhang; Shao Po Wang; Jing Jie Yu (Desalination and Water Treatment)
In previous studies, microwave irradiation mostly focused on the demulsification of crude oil or artificially prepared emulsion with water content less than 50 %. For cutting fluid wastewater (CFW) with a water content about 99 %, this study researched the relationship among microwave irradiation duration, microwave power, and the irradiated CFW temperature, as well as their impact on the particle size, COD, and zeta potential of the irradiated CFW, and results showed that the optimal demulsification temperature was all in 70–80℃ for microwave irradiation demulsifying CFW. By comparing the energy efficiency (φ) and the proportion of volatile COD of the irradiated CFW to the total COD (ηv-COD) under each power, it was found that φ was highest and ηv-COD was lowest at 600 W. The CFW contained heterocyclic and aromatic compounds before and after microwave irradiation, and the raw CFW also contained 61.35 % organics with MW > 100 kDa and 22.56 % organics with MW < 1 kDa. After microwave irradiation under the optimal operation conditions, 70.43 % oil and 26.71 % COD volatilized into the air. Due to the release of small molecule organics from the demulsified droplets or the breakage of macromolecular organics at high temperatures, the COD proportion of organics with MW 50–10 kDa, 10–5 kDa, 5–1 kDa, and < 1 kDa increased, and the B/C of the irradiated CFW also rose from 0.13 to 0.20, when compared with the raw CFW.